2016
DOI: 10.3847/0004-637x/822/2/87
|View full text |Cite
|
Sign up to set email alerts
|

Instability of Non-Uniform Toroidal Magnetic Fields in Accretion Disks

Abstract: A new type of instability that is expected to drive magnetohydrodynamic (MHD) turbulence from a purely toroidal magnetic field in an accretion disk is presented. It is already known that in a differentially rotating system, the uniform toroidal magnetic field is unstable due to a magnetorotational instability (MRI) under a non-axisymmetric and vertical perturbation, while it is stable under a purely vertical perturbation. Contrary to the previous study, this paper proposes an unstable mode completely confined … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Although the destabilizing mechanism for Model A remains unresolved, the instability seems to be relevant to the magnetogradient-driven instability proposed by Hirabayashi & Hoshino (2016). This instability is driven by the expansive nature of the magnetic pressure gradient force arising from a nonuniform toroidal field.…”
Section: Possible Destabilizing Mechanism For the Case Of The Rapidly...mentioning
confidence: 92%
See 1 more Smart Citation
“…Although the destabilizing mechanism for Model A remains unresolved, the instability seems to be relevant to the magnetogradient-driven instability proposed by Hirabayashi & Hoshino (2016). This instability is driven by the expansive nature of the magnetic pressure gradient force arising from a nonuniform toroidal field.…”
Section: Possible Destabilizing Mechanism For the Case Of The Rapidly...mentioning
confidence: 92%
“…However, the unstable condition is not satisfied for Model A. As we will discuss in Section 4.5, the instability seems to be relevant to the magneto-gradient-driven instability proposed by Hirabayashi & Hoshino (2016).…”
Section: Magnetospheric Boundarymentioning
confidence: 93%
“…It is already known that, in a differentially rotating system, the uniform toroidal magnetic field is unstable due to MRI under a non‐axisymmetric and vertical perturbation, while it is stable under a purely vertical perturbation. Hirabayashi and Hoshino found that the expansive nature of the magnetic pressure gradient force under a non‐uniform toroidal field would lead a purely vertical perturbation to be unstable.…”
Section: Introductionmentioning
confidence: 99%